Direct blood PCR in combination with nucleic acid lateral flow immunoassay for detection of Plasmodium species in settings where malaria is endemic. - Mens, P; de Bes, H; Sondo, P; Laochan, N; Keereecharoen, L; van Amerongen, A; Flint, J; Sak, JR; Proux, S; Tinto, H; Schallig, H (2012)
Declining malaria transmission and known difficulties with current diagnostic tools for malaria, such as microscopy and rapid diagnostic tests (RDTs) in particular at low parasite densities, still warrant the search for sensitive diagnostic tests. Molecular tests need substantial simplification before implementation in clinical settings in countries where malaria is endemic. Direct blood PCR (db-PCR), circumventing DNA extraction, to detect Plasmodium was developed and adapted to be visualized by nucleic acid lateral flow immunoassay (NALFIA). The assay was evaluated in the laboratory against samples from confirmed Sudanese patients (n = 51), returning travelers (n = 214), samples from the Dutch Blood Bank (n = 100), and in the field in Burkina Faso (n = 283) and Thailand (n = 381) on suspected malaria cases and compared to RDT and microscopy. The sensitivity and specificity of db-PCR-NALFIA compared to the initial diagnosis in the laboratory were 94.4% (95% confidence interval [CI] = 0.909 to 0.969) and 97.4% (95% CI = 0.909 to 0.969), respectively. In Burkina Faso, the sensitivity was 94.8% (95% CI = 0.88.7 to 97.9%), and the specificity was 82.4% (95% CI = 75.4 to 87.7%) compared to microscopy and 93.3% (95% CI = 87.4 to 96.7%) and 91.4% (95% CI = 85.2 to 95.3%) compared to RDT. In Thailand, the sensitivity and specificity were 93.4% (CI = 86.4 to 97.1%) and 90.9 (95% CI = 86.7 to 93.9%), respectively, compared to microscopy and 95.6% (95% CI = 88.5 to 98.6%) and 87.1% (95% CI = 82.5 to 90.6) compared to RDT. db-PCR-NALFIA is highly sensitive and specific for easy and rapid detection of Plasmodium parasites and can be easily used in countries where malaria is endemic. The inability of the device to discriminate Plasmodium species requires further investigation.